PERBANTUAN TNI KEPADA PEMERINTAH DAERAH - Ryllian Chandra (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
This study examines focus to TNI assistance to local authorities as Military Operations Other Than War (MOOTW). One of the main points that must be seen in the improvement of the defense sector is the assistance of TNI to local authorities. At the central level TNI considered could not political anymore, but doesnt mean that the military has no longer political interests. The starting point of this study was the question at a point in the task of Military Operations Other Than War (MOOTW) carried out according to TNI Law No.34/2004. The purpose of this study was to determine how the military politics in their assistance to local authorities. Keywords : Military Operations Other Than War, Politics Military, Local Government